2021
DOI: 10.3390/nu13124359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute and Chronic Oral l-Carnitine Supplementation on Exercise Performance Based on the Exercise Intensity: A Systematic Review

Abstract: l-Carnitine (l-C) and any of its forms (glycine-propionyl l-Carnitine (GPL-C) or l-Carnitine l-tartrate (l-CLT)) has been frequently recommended as a supplement to improve sports performance due to, among others, its role in fat metabolism and in maintaining the mitochondrial acetyl-CoA/CoA ratio. The main aim of the present systematic review was to determine the effects of oral l-C supplementation on moderate- (50–79% V˙O2 max) and high-intensity (≥80% V˙O2 max) exercise performance and to show the effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 53 publications
(250 reference statements)
0
5
0
Order By: Relevance
“…[ 43 ] It produces effects similar to those of an antidepressant, helping to swiftly maintain and repair aberrant hippocampal glutamate function and dendritic plasticity, which assists in the tailored treatment of major depression subtypes. [ 44 ] Furthermore, during high‐intensity exercise, its stabilizing action on the mitochondrial acetyl coenzyme A/CoA ratio mitigates the impacts on performance measures. [ 45 ] Acute myocardial infarction (AMI) has been treated by regulating the amounts of lipid coenzyme A, which is thought to be an essential metabolic cofactor in physiology.…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] It produces effects similar to those of an antidepressant, helping to swiftly maintain and repair aberrant hippocampal glutamate function and dendritic plasticity, which assists in the tailored treatment of major depression subtypes. [ 44 ] Furthermore, during high‐intensity exercise, its stabilizing action on the mitochondrial acetyl coenzyme A/CoA ratio mitigates the impacts on performance measures. [ 45 ] Acute myocardial infarction (AMI) has been treated by regulating the amounts of lipid coenzyme A, which is thought to be an essential metabolic cofactor in physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Doses of 3 to 4 g of L-carnitine or glycine propionyl-L-carnitine (GPL-C) consumed between 60 and 90 min prior to exercise could increase the lactate threshold, reduce perceived exertion throughout incremental tests until exhaustion, and increase peak and average power in the Wingate cycle ergometer test. [ 14 ] In another study, the considerable effects of L-carnitine administration on preventing muscle atrophy were shown. [ 15 ] In the aforementioned study, it was concluded that acetyl L-carnitine at a dose of 1,500 mg/day had a significant effect on the reduction of neuropathic pain with promising results in compressive neuropathy caused by carpal tunnel syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…L-carnitine (LC) is a molecule that transports long-chain fatty acids into the mitochondria for fat oxidation and is derived mostly from dietary intake (1)(2)(3). A prior study has suggested that LC is involved in inflammatory pathway mediation by reducing inflammatory cytokines (4)(5)(6). By reducing inflammation, oxidative stress, and myocyte necrosis, LC may thus provide cardioprotective effects (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%